Identification of nonlinearity in bolted beam using response-controlled testing and force-controlled testing / Khairul Aiman Khairul Anuar ... [et al.] - Khairul Anuar, Khairul Aiman; Bahari, Abdul Rahim; Abdul Rani, Muhamad Norhisham; Konstantinos, Rousou; Andreas, Kyprianou (UiTM Press, 2024)
Nonlinear phenomena such as super-and sub-harmonics and unstable branches in frequency response functions (FRFs) often occur in slender structures, which are common in the aerospace, civil and wind power domains. The widely used methods of linear modal analysis are invalid for the identification of these phenomena, which play an important role in nonlinear structural analysis as they can significantly affect the behaviour and stability of structures under various excitations. This paper proposes the methodology of Response-Controlled Stepped Sine Testing (RCT) and Force-Controlled Stepped Sine Testing (FCT) to identify nonlinear phenomena in a bolted beam. The bolted beam was excited with two different sets of predefined displacement and force amplitudes to measure the Nonlinear Frequency Response Functions (NLFRFs) of the bolted beam. The measurements were performed with RCT and FCT, using Stepped Sine signals to control the displacement and force amplitudes. The Harmonic Force Surface (HFS) technique was used as means of obtaining the NFRFs. It was found that RCT with HFS successfully identified the nonlinearity that is very similar to the identification results obtained with FCT. In addition, RCT was computationally faster than FCT in identifying nonlinear bolted beams and avoided dealing with jump phenomena. These advantages of RCT and HFS can provide engineers and researchers with a great technique to accurately and efficiently identify nonlinearities in structures.